Power-and Current-Based Control of Distributed Inverters in Low-Voltage Microgrids: Considerations in Relation to Classic Droop Control - Marafao, Fernando P. [UNESP]; Alonso, Augusto M. S. [UNESP]; Gothner, Fredrik; Tedeschi, Elisabetta; Brandao, Danilo I. (Institute of Electrical and Electronics Engineers (IEEE), 2020)
This paper addresses the matter of active and reactive power sharing among distributed inverters in low-voltage microgrids, particularly highlighting the peculiarities of two strategies of coordinated control based on a master/slave architecture, namely Power-and Current-Based Control, in comparison to the classic droop control approach. It is demonstrated that the Power-and Current-Based Control strategies present distinct operational features in relation to classic droop control, mostly concerning how active and reactive power are shared among inverters. Additionally, it is shown how the strategies differ in steady-state operation and response time while comparing to classic droop-based methods. Discussions are presented based on simulation results using Matlab/Simulink, comprising two distributed inverters in a low-voltage microgrid and considering different operational scenarios, such as load changes, existence of linear and nonlinear loads, as well as line impedance variations. Experimental results are presented to validate the expected behavior of one of the strategies.
Keywords: Current-Based Control; droop control; microgrids; power sharing; Power-Based Control